2011
DOI: 10.1007/s00246-011-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

Early NT-proBNP Is Able to Predict Spontaneous Closure of Patent Ductus Arteriosus in Preterm Neonates, But Not the Need of Its Treatment

Abstract: The objective of this study was to establish the potential utility of N-terminal pro-brain natriuretic peptide (NT-proBNP) in the management of patent ductus arteriosus (PDA). This was a monocentric prospective blind study that was conducted in a referral neonatal intensive care unit. The patients were very low-birth-weight/gestational-age neonates. Babies with cardiac congenital anomaly other than PDA, life-threatening congenital malformation, severe asphyxia at birth, persistent pulmonary hypertension, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Therefore, high levels of serum NT-proBNP do not allow determining infants that need pharmacological treatment. A similar conclusion was made by Martinovici et al [23] who showed that serum NT-proBNP level below the cutoff of 10,000 pg/ml on the second day of life was associated (89% sensitivity and 100% specificity) with spontaneous DA closure within the first week of life. Yet, any value above this threshold, as a single marker, could not identify neonates who would benefit from targeted PDA treatment [23].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, high levels of serum NT-proBNP do not allow determining infants that need pharmacological treatment. A similar conclusion was made by Martinovici et al [23] who showed that serum NT-proBNP level below the cutoff of 10,000 pg/ml on the second day of life was associated (89% sensitivity and 100% specificity) with spontaneous DA closure within the first week of life. Yet, any value above this threshold, as a single marker, could not identify neonates who would benefit from targeted PDA treatment [23].…”
Section: Discussionsupporting
confidence: 84%
“…proBNP value to predict early spontaneous DA closure in very preterm infants with PDA diameter >1.5 mm who were not treated [22,23]. This difference could be explained by the fact that in our study, for the first time the appropriate predictive value of serum NT-proBNP concentrations was evaluated in a randomized group of infants who were managed expectantly.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies have showed that the NT-proBNP level on Day-1 of life was affected by gestational age with the level being higher in the more premature infants. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Infants <1 month of age were also excluded because NTproBNP is extremely high in this group. 10 This study was approved by the hospital ethics committee and written informed consent was obtained from the patients' parents for participation.…”
mentioning
confidence: 99%